Molecular Characterization of Yarrowia lipolytica and Candida zeylanoides Isolated from Poultry - Deak, T. (American Society for Microbiology, 2000)
Yeast isolates from raw and processed poultry products were characterized using PCR amplification of the internally transcribed spacer (ITS) 5.8S ribosomal DNA region (ITS-PCR), restriction analysis of amplified products, randomly amplified polymorphic DNA (RAPD) analysis, and pulsed-field gel electrophoresis (PFGE). ITS-PCR resulted in single fragments of 350 and 650 bp, respectively, from eight strains of Yarrowia lipolytica and seven strains of Candida zeylanoides. Digestion of amplicons with HinfI and HaeIII produced two fragments of 200 and 150 bp from Y. lipolytica and three fragments of 350, 150, and 100 bp from C. zeylanoides, respectively. Although these fragments showed species-specific patterns and confirmed species identification, characterization did not enable intraspecies typing. Contour-clamped heterogeneous electric field PFGE separated chromosomal DNA of Y. lipolytica into three to five bands, most larger than 2 Mbp, whereas six to eight bands in the range of 750 to 2,200 bp were obtained from C. zeylanoides. Karyotypes of both yeasts showed different polymorphic patterns among strains. RAPD analysis, using enterobacterial repetitive intergenic sequences as primers, discriminated between strains within the same species. Cluster analysis of patterns formed groups that correlated with the source of isolation. For ITS-PCR, extraction of DNA by boiling yeast cells was successfully used.